(3GdefUU TQM GdedNU (B( (3aj GdMceI hGdefWb (B)s - (3Ydj Hf YeQ Hf Ydj GdcGJHj GdbRhjfj, fLe GdOjf, hjbGd dg OHjQGf , (B675 (3g` s; (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3Ydi Hf GdaGSi Hf Ydi GdWHQi s)
(3ChdgG (B:s
(3GdMeO dehLO ChLO HbOQJg GdJGeI GLfGS GdehLhOGJ s
(3BNQgG (B:s
(3hGYde Gf GdNdGU Yf gPg GdTHgGJ djS GdG hdjcf gPG BNQ cdGefG ai gPg GdeSFdI hHg Je LejY cJG H s
(3fSNI fajSgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1819s
Keywords: (3GdadSaI hGdefWbs